(untitled) (Scientific journal of the Fergana State University, 2025)
This article analyzes the research contributions of prominent modern onomasticians Richard Coates, Patrick Hanks, Ernest Weekley, and David Mills. Their works on the etymology, historical development, and linguistic aspects of personal names, surnames, and place names are examined. Additionally, the article discusses their contributions to the fields of onomastics and linguistics